Moderate Alcohol Exposure during the Rat Equivalent to the Third Trimester of Human Pregnancy Alters Regulation of GABAA Receptor-Mediated Synaptic Transmission by Dopamine in the Basolateral Amygdala - Diaz, Marvin Rafael; Jotty, Karick; Locke, Jason L.; Jones, Sara R.; Valenzuela, Carlos Fernando (Frontiers in Pediatrics, 2014)
Fetal ethanol (EtOH) exposure leads to a range of neurobehavioral alterations, including deficits in emotional processing. The basolateral amygdala (BLA) plays a critical role in modulating emotional processing, in part, via dopamine (DA) regulation of GABA transmission. This BLA modulatory system is acquired during the first two weeks of postnatal life in rodents (equivalent to the 3rd trimester of human pregnancy) and we hypothesized that it could be altered by EtOH exposure during this period. We found that exposure of rats to moderate levels of EtOH vapor during the 3rd trimester-equivalent (postnatal days (P) 2-12) alters DA modulation of GABAergic transmission in BLA pyramidal neurons during periadolescence. Specifically, D1R-mediated potentiation of spontaneous inhibitory postsynaptic currents (IPSCs) was significantly attenuated in EtOH-exposed animals. However, this was associated with a compensatory decrease in D3R-mediated suppression of miniature IPSCs. Western blot analysis revealed that these effects were not a result of altered D1R or D3R levels. BLA samples from EtOH-exposed animals also had significantly lower levels of the DA precursor (L-3,4-dihydroxyphenylalanine) but DA levels were not affected. This is likely a consequence of reduced catabolism of DA, as indicated by reduced levels of 3,4-dihydroxyphenylacetic acid and homovanillic acid in the BLA samples. Anxiety-like behavior was not altered in EtOH-exposed animals. This is the first study to demonstrate that the modulatory actions of DA in the BLA are altered by developmental EtOH exposure. Although compensatory adaptations were engaged in our moderate EtOH exposure paradigm, it is possible that these are not able to restore homeostasis and correct anxiety-like behaviors under conditions of heavier EtOH exposure. Therefore, future studies should investigate the potential role of alterations in the modulatory actions of DA in the pathophysiology of fetal alcohol spectrum disorders.